L’intégration des cueilleurs de déchets latino-américains ou la création d’une nouvelle marge - Mathieu Durand; Fabio De Oliveira Neves (EchoGéo)
For decades, Latin American cities have been fighting against informal wastepickers, prioritizing sanitary safety and hygienist logic. Today, struggles against the waste of resources and against poverty lead recognition of wastepickers activities. These "gatherer" of waste, acting in an autonomous way, are today the principal preoccupation of municipal recycling policies in Latin America. However, the limits of this model appear quickly. The integration of informal wastepickers implies, in each city, appear of new margins because of waste capture waste. What relationships are then established between the stakeholders? Peru, Colombia and Brazil will illustrate this issue.